2019
DOI: 10.1103/physreva.100.013811
|View full text |Cite
|
Sign up to set email alerts
|

Squeezed displaced entangled states in the quantum Rabi model

Abstract: The quantum Rabi model accepts analytical solutions in the so-called degenerate qubit and relativistic regimes with discrete and continuous spectrum, in that order. We show that solutions are the superposition of even and odd displaced number states, in the former, and infinitely squeezed coherent states, in the latter, of the boson field correlated to the internal states of the qubit. We propose a single parameter model that interpolates between these discrete and continuous spectrum regimes to study the spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…[ 95 ] In such a case, the spectral collapse occurs at a critical value of the coupling strength g=gnormalt/2. [ 95,99 ] Other nonlinear process, such as quantum Rabi–Stark model, [ 64,100–103 ] can also cause spectrum collapse. [ 101,102 ] As extensions, bias two‐photon QRM [ 104 ] and multiphoton QRM [ 28,98,105,106 ] have also been explored.…”
Section: Quantum States In Polaron Picturementioning
confidence: 99%
“…[ 95 ] In such a case, the spectral collapse occurs at a critical value of the coupling strength g=gnormalt/2. [ 95,99 ] Other nonlinear process, such as quantum Rabi–Stark model, [ 64,100–103 ] can also cause spectrum collapse. [ 101,102 ] As extensions, bias two‐photon QRM [ 104 ] and multiphoton QRM [ 28,98,105,106 ] have also been explored.…”
Section: Quantum States In Polaron Picturementioning
confidence: 99%
“…Thus forming a long-lived pair when we move into a dissipative setting. Since their structure is inherited from the two-excitation processes (cat-states are eigenstates of the parity e in and two-photon annihilation â2 operators making them ubiquitous in systems driven by twophoton transitions [41][42][43][44][45]), it can then be expected for low-energy states outside the crossing to mantain this form deep into the strong coupling regime (Sec. IV).…”
Section: A Dressed States At the First Energy Crossingmentioning
confidence: 99%
“…In the past, we showed that a competition between Hamiltonians with components showing discrete and continuous spectrum produces the spectral collapse in the single-photon quantum Rabi model [21]. There, the collapse occurs from the transition from driven-cavitylike, in the degenerate-qubit regime, into a relativistic (1 + 1)D Dirac-like Hamiltonian, in the relativistic regime.…”
Section: Optical Phase Space Modelmentioning
confidence: 99%
“…An interesting characteristic of the single-photon quantum Rabi model is the spectral collapse that occurs in the so-called relativistic regime [21]. There, we can follow the transition from a discrete spectrum in the so-called degenerate qubit regime where the model is equivalent to a driven cavity and the so-called relativistic regime where the model is equivalent to Dirac equation in (1 + 1)D with continuous spectrum.…”
Section: Introductionmentioning
confidence: 99%

Spectral Collapse in the two-photon quantum Rabi model

Rico,
Maldonado-Villamizar,
Rodriguez-Lara
2019
Preprint
Self Cite